Single molecule electronic devices with carbon-based materials: status and opportunity. Issue 2 (6th January 2021) - Ghasemi, Shima; Moth-Poulsen, Kasper
Abstract : The field of single molecule electronics has progressed remarkably in the past decades by allowing for more versatile molecular functions and improving device fabrication techniques. Abstract : The field of single molecule electronics has progressed remarkably in the past decades by allowing for more versatile molecular functions and improving device fabrication techniques. In particular, electrodes made from carbon-based materials such as graphene and carbon nanotubes (CNTs) may enable parallel fabrication of multiple single molecule devices. In this perspective, we review the recent progress in the field of single molecule electronics, with a focus on devices that utilizes carbon-based electrodes. The paper is structured in three main sections: (i) controlling the molecule/graphene electrode interface using covalent and non-covalent approaches, (ii) using CNTs as electrodes for fabricating single molecule devices, and (iii) a discussion of possible future directions employing new or emerging 2D materials.